2010
DOI: 10.1007/s12070-010-0055-z
|View full text |Cite
|
Sign up to set email alerts
|

Effective Treatment of Acute Otitis Externa: a Comparison of Steroid Antibiotic Versus 10% Ichthammol Glycerine Pack

Abstract: To compare the efficacy of treatment between steroid-antibiotic and 10% Ichthammol glycerine packs (IG packs) in acute otitis externa. A prospective, randomized clinical trial between steroid-antibiotic and 10% IG pack which was performed in department of ENT-HNS, Kathmandu University Hospital, Dhulikhel from July 2009 to December 2009 on 82 patients. Pain was assessed by Numerical Rating Scale (NRS) and edema was assessed by dividing the external auditory canal in four quadrant giving score of 25% for each on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Our study showed acute o s externa more in female than male with incidence of 1.29 mes higher. The result of our study substan ate with the study done by BL Shrestha et al 19 where he also observed incidence higher in female. 20 Jamalullah M et al has male incidence higher than female.…”
Section: Discussionsupporting
confidence: 75%
“…Our study showed acute o s externa more in female than male with incidence of 1.29 mes higher. The result of our study substan ate with the study done by BL Shrestha et al 19 where he also observed incidence higher in female. 20 Jamalullah M et al has male incidence higher than female.…”
Section: Discussionsupporting
confidence: 75%
“…But there was no statistically significant difference in the efficacy of both the groups compared to each other. Although, as discussed already, other similar study by Bhatta et al [20] and by Shrestha et al [14] have shown that steroid-antibiotic pack is better for earlier relief of pain leading to decrease number of hospital visits in the management of acute otitis externa.…”
Section: Discussionmentioning
confidence: 81%
“…Studies have shown the use of topical antibiotics [10] , topical steroid [11,12] , or a combination of topical antibiotic and steroid [13] as the initial treatment of otitis externa. But very few studies have directly compared the use of glycerol and ichthammol combination with other forms of topical medications [14,15,16] . This prospective randomized study has been undertaken to compare the efficacy of ichthammol glycerin pack with steroid antibiotic pack as the initial treatment for acute otitis externa.…”
Section: Introductionmentioning
confidence: 99%
“…Shrestha et al in a study observed that steroid -an bio c was more effec ve than 10% icthammol glycerine 18 on seven day visit. The study cured all pa ents within ten days of treatment but no sta s cally significant differences in cure rates were recorded between the two groups.…”
Section: Resultsmentioning
confidence: 98%
“…Similarly, study conducted by Joseph et al revealed that number of male pa ents was 1.07 mes higher than female pa ents. In a study by Shrestha et al observed that [16][17][18] the incidence was 1.05 mes higher in female pa ents. However, the study of Gercek et al showed no correla on between genders and AOE as the pathology of OE is not 19 influenced by hormones.…”
Section: Discussionmentioning
confidence: 99%